A review of Paul Lassenius Kramp’s hydrozoan types (taxonomic status, location and condition of the material) and a biography of the Danish zoologist - Gravili, Cinzia; Pavesi, Laura; Boero, Ferdinando; Tendal, Ole S. (Zootaxa, 2018)
During his scientific career, largely from 1910–1970, the Danish cnidarian specialist P.L. Kramp authored 94 scientific papers, and more than 30 other kinds of publications, such as reports and popular articles. Kramp was affiliated with the marine department of the Zoological Museum of the University of Copenhagen (now: The Natural History Museum of Denmark, NHMD), an institution intensely involved at the time in expeditions, in the assembling and maintenance of collections, and in the revision of a wide range of animal groups. Kramp took part in several expeditions in different parts of the world. He had opportunities to receive training in sampling and preservation techniques, to perform observations on living or at least freshly preserved material, and to collect specimens. Kramp dedicated most of his long career to studying the taxonomy of medusae, with some attention also to their polyp stages, describing 101 nominal hydrozoan taxa, including one order, four families and fifteen genera. Sixty-five of these taxa (one order, three families, twelve genera, 48 species and one subspecies) are still accepted in the original nominal form. Kramp raised the international reputation of his museum and his scientific results are still appreciated today.